The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jfoodeng.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ thermal treatment in fluidised bed. Experimental study and mathematical modelling of the heat and mass transfer

Abstract: Wheat germ is an abundant by-product of the milling industry, it has excellent nutritional qualities and high tocopherols content. The aim of this work was to study the kinetics of wheat germ drying in fluidised thin-layers by applying analytical solutions of the diffusion equation. Also, was determined the effective heat transfer coefficient by solving the macroscopic energy balance to contribute with the design and optimization of a thermal treatment for this product. Four air temperatures were studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…The local sensitivity analysis approach was used to verify the model parameter. The criterion of the model verification was calculated by using the minimum of the absolute average deviation (AAD) [31]. The equation is defined as…”
Section: Response Of the Moisture Content Of Wheat Germmentioning
confidence: 99%
See 1 more Smart Citation
“…The local sensitivity analysis approach was used to verify the model parameter. The criterion of the model verification was calculated by using the minimum of the absolute average deviation (AAD) [31]. The equation is defined as…”
Section: Response Of the Moisture Content Of Wheat Germmentioning
confidence: 99%
“…An empirical type provides a direct relationship between average MC and time, but it neglects the physical correlation between the drying processes and their parameters [26]. Gili et al [31] successfully developed an analytical series solution for the microscopic diffusion equations and applied a theoretical thin-layer model coupling with a macro-heat transfer model to predict the MC of WG during drying in the FBD. They also observed that the moisture loss occurred in the falling drying rate period for WG drying in the FBD.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat germ is another mass-produced by product from wheat milling processing and containing many nutrients, such as carbohydrate, protein, fat, vitamins and minerals [39,80]. However, fresh wheat germ is not able to bear a long-term storage due to unsaturated fats and endogenous enzyme with high moisture content causing rancidity, which is produced by oxidation reaction [81].…”
Section: Wheat Germ Dryingmentioning
confidence: 99%
“…Different drying processes are used to overcome this problem and the numerical method was also applied. Gili et al studied the dehydration of wheat germ using a fluidized bed dryer with both mathematical modeling and experiment measurements [80]. In their experiment, the fluidized bed dryer was employed at different temperatures (90,110,130 and 150 • C) at constant air velocity (0.5 m/s) [80].…”
Section: Wheat Germ Dryingmentioning
confidence: 99%
See 1 more Smart Citation